P497 Early improvement in bowel wall thickness on transperineal ultrasonography predicts treatment success in active ulcerative colitis. (21st January 2022) - Sagami, S; Kobayashi, T; Aihara, K; Umeda, M; Odajima, K; Morikubo, H; Asonuma, K; Miyatani, Y; Fukuda, T; Matsubayashi, M; Kiyohara, H; Nakano, M; et al.
Abstract: Background: Bowel ultrasonography is a non-invasive imaging tool that can repeatedly monitor the activity of ulcerative colitis (UC). This study aimed to determine whether early changes in bowel ultrasonographic findings could predict subsequent clinical response to induction treatment in patients with ulcerative colitis. Methods: This single-center prospective study compared ultrasonographic findings with fecal calprotectin, and C-reactive protein (measured at baseline, week 1, and week 8) in predicting remission (patient-reported outcome-2 ≤ 1 with no rectal bleeding subscore) at week 8 in active UC patients who initiated the remission-induction treatments. Predictive factors were assessed using multivariate regression models and a receiver operating curve analysis. Results: A total of 100 patients were analysed, of which 54 achieved remission at week 8. Baseline values of biomarkers, and ultrasonographic parameters were not predictive of remission. Bowel wall thickness and bowel wall flow at baseline and week 1 were also not sufficiently predictive. By contrast, changes from baseline to week 1 in bowel wall thickness in the rectum measured by transperineal ultrasonography was an independent predictor of remission by week 8 (adjusted odds ratio associated with 1 mm decrease: 1.90 (95% confidence interval 1.22–2.95)). Predictive value of changes in rectal bowel wall thickness remained high for clinical improvement even among patients who did not achieve remission in 1 week. Conclusion: Improvement in rectal bowel wall thickness measured by transperineal ultrasonography at week 1 predicts treatment success and thus would help decision making during the early course of induction treatment in UC.